Modelagem matemática na gestão ambiental fluvial: simulação dos impactos no sistema receptor de efluentes, para orientar operação de tratamento de esgoto, sujeito a variações meteorológicas transitórias - Reda, André Luiz de Lima (Revista Gestão da Produção Operações e Sistemas, 2006)
This paper demonstrates a mathematical modeling technique for fluvial water quality subject to transitoryimpacts from poured sewage after gales, developed to “unitary systems” (sewage along with rain drainage, in oldand cold countries – North Hemisphere), which is useful to guide, in real time, decisions for the treatmentoperation of this sewage. By integrating an international research line, this technique may also serve, along withoptimization tools, to real-time planning and management of fluvial systems with transitory disturbances byseveral reasons.Originally, it would not be applied to Brazil: at the end of the 19th Century, it was established inthe country a well-intended preference for collecting sewage in a public network apart from the drainage – thelatter is subject to tropical downpour. However, despite such philosophy being still predominant in projects, theaging of the two systems and irregularities continuously introduced in land and public facilities has beenpromoting an increasing promiscuity between both of them (examples: illegal connections, underground leaking)and elevated flow rates led after gales towards treament stations to the extent of having their capacitiesoverflown. This way, the proposed simulation technique is useful to the Brazilian context. Its employment isdemonstrated in a real case, by a ranking of the treatment operation alternatives based on the resulting fluvialquality simulations – therefore, aiming at an environmental objective.Keywords: Mathematical simulation of the fluvial water quality; Impacts of the sewage on rivers; Hydricsystem environmental management.